Do East Asians With Normal Glucose Tolerance Have Worse β-Cell Function? A Meta-Analysis of Epidemiological Studies - Li, Li; Zou, Xiantong; Huang, Qi; Han, Xueyao; Zhou, Xianghai; Ji, Linong (Frontiers in Endocrinology, 2021)
Background The difference in the relationship between β-cell function and insulin resistance among Africans, Caucasians and East Asians with normal glucose tolerance (NGT) was not well investigated. Methods We searched PubMed and Web of Science with keywords and identified studies that used the homeostasis model assessment (HOMA) model to evaluate β-cell function (HOMA-B) and insulin sensitivity/resistance (HOMA-S/HOMA-IR) in certain ethnic groups. We used the random-effect model to pool data of HOMAs and compared the combined data among the three ethnic groups using subgroup analysis. Linear regression analysis was used to estimate the coefficient of HOMA-S on HOMA-B in these ethnic groups. Results We evaluated pooled data of HOMAs in eight African, 26 Caucasian and 84 East Asian cohorts with NGT, including 2392, 6645 and 67317 individuals, respectively. The three ethnic groups had distinct HOMA-B but similar HOMA-IR. The regression coefficient of lnHOMA-B on lnHOMA-S was different between Africans and Caucasians (-1.126 vs -0.401, P=0.0006) or East Asian (-1.126 vs. -0.586, P=0.0087), but similar between Caucasians and East Asians (-0.401 vs. -0.586, P=0.1282). The coefficient in all ethnic groups was similar when age and BMI were adjusted (African vs Caucasian P=0.0784, African vs East Asian P=0.1136, Caucasian vs East Asian P=0.4827). Conclusions In subjects with NGT, East Asians had lower HOMA-B, but had similar β-cell response relative to insulin resistance with Caucasians and Africans when age and BMI were controlled. This result may challenge the allegation that there was an Asian specific diabetes phenotype with worse β-cell function.